Challenging Discourses of Sexual Violence on X: The Linguistic Representation of Victims and Perpetrators in Kavanaugh’s Confirmation Process - Patricia Palomino Manjón (Revista Alicantina de Estudios Ingleses)
In September 2018, American Justice Brett Kavanaugh was accused of sexual assault by Dr. Christine Blasey Ford during his nomination to the US Supreme Court. The sexual allegations provoked a crisis in American society concerning the rights of female American citizens and created a heated debate among X (formerly Twitter) users, who commented on the event and expressed their (dis)affiliation. Research has shown that X is one of the most sexist and abusive social media services due to the constant spread and negotiation of different discourses relating to rape culture on the platform (Mendes et al. 2018). Consequently, the objectives of this research are to examine the linguistic patterns and discourses employed by X users to denounce patriarchal oppression and negotiate the identities of the different social actors involved in Kavanaugh’s confirmation process. To do so, two datasets of posts (previously known as ‘tweets’) containing the opposing hashtags #KavanaughConfirmation and #NoKavanaughConfirmation were analyzed and contrasted drawing on Corpus-Assisted Discourse Analysis tools (i.e., keywords and concordances) (Partington et al. 2013) and Feminist Critical Discourse Analysis (Lazar 2005). The results revealed a high presence of keywords concerning gender and violence to construct identities of victims and perpetrators. However, not only were such identities related to sexual violence but also political and institutional violence. In addition, the analysis revealed the creation of discursive protests on X to resist patriarchal discourses and practices in American society.